EFFICACY OF ADALIMUMAB IN EARLY RHEUMATOID ARTHRITIS IN RELATION TO ITS SERUM LEVEL AND THE PRESENCE OF ANTI-DRUG ANTIBODY - A. S. Avdeeva; E. N. Aleksandrova; D. E. Karateev; E. L. Luchikhina; A. A. Novikov; M. V. Cherkasova; E. L. Nasonov (Научно-практическая ревматология)
Objective: to assess the relationship of the efficiency of adalimumab (ADA) therapy in early rheumatoid arthritis (RA) with the serum level of the drug and with the presence of antibody (Ab) to it.Subjects and methods. Serum concentration of ADA and Ab against it (μg/ml) were measured using an enzyme immunoassay in 25 patients with early RA before, 12 and 24 weeks after beginning of the therapy. All patients received the disease-modifying antirheumatic drug methotrexate and ADA 40 mg subcutaneously every other week. ADA was the first biological agent for all patients.Results. The patients were divided into the following groups: those with a serum ADA level of <2.85 (Group 1, n=7) and ≥2.85 (Group 2, n=13). After 24 weeks of treatment, Group 1 showed higher disease activity (DAS was 4.5 [3.3; 4.9]) and levels of acute-phase reactants (ESR, 44 [18; 57] mm/hr; C-reactive protein (CRP), 10.1 [4.9; 34.5] mg/ml) than Group 2 (3.5 [2.9; 3.9], 15.0 [6.0; 17.0] mm/hr, 1.9 [0.75; 6.7] mg/ml, respectively; p<0.05). Also, after24 weeks of therapy, there was a negative correlation of ADA level and DAS28 (r=-0.46; p=0.04), CRP (r=-0.54;p=0.02) and ESR (r=-0.5; p=0.02). Anti-ADA Ab were found in 3 and 2 patients after 12 and 24 weeks, respectively. After 24 weeks of therapy, allpatients with anti-ADA Ab exhibited no clinical effect. There were few unresponsive patients (11%) among those without anti-ADA Ab.Conclusion. In patients with early RA treated with ADA, its low serum level (<2.85 μg/ml) is associated with the higher clinical and laboratory measures of disease activity. After 12–24 weeks of ADA therapy, 10–12.5% of patients are found to have Ab to the drug and its production is associated with lower efficacy.